I am looking for a proof that omitted variable bias (OVB) in OLS regression may lead to endogeneity. I have found many examples here and out there on how to prove that a given parameter $b_{j}$ (where $j=1,...,J$ parameters in the model) gets biased, for instance these two threads:

But this is not exactly what I want. What I want is a more generic proof that a given variable $X_j$ gets correlated with the error term $e$ when there is OVB, i.e., that ${\rm Cov}(X_j,e) \ne 0$.

For instance, let's say the correct equation would be: $$Y = b_0 + b_1 X_1 + b_2 X_2 + b_3 X_3 + u$$ But we estimate the following: $$Y = b_0 + b_1 X_1 + b_2 X_2 + e,$$ where we are omitting $X_3$ and of course its coefficient $b_3$.

Assuming that ${\rm Cov}(X_3, X_2) \ne 0$, how is it possible to prove that ${\rm Cov}(X_2,e) \ne 0$ and therefore $X_2$ is endogenous due to OVB, instead of just calculating the amount of bias in $b_2$?

  • 2
    $\begingroup$ $e=b3X3+u$, so $cov(X2,e)=cov(X2,b3X3+u)$=$b3cov(X2,X3)$ which is not equal to zero, as long as $b3$ is not equal to zero. Proved. $\endgroup$
    – user227710
    Mar 6, 2014 at 23:22

1 Answer 1


To prove this, start from the probability limit of the OLS estimator. Let $X$ denote the full matrix of regressors to be used, $[1,X_1,X_2]$, and let $e \equiv u + b_3 X_3$. Also, let $b$ be the parameters we are trying to estimate, i.e. $b = (b_0,b_1,b_2)$.

\begin{align*} p\lim \hat{\beta} &= p\lim \left[ (X'X)^{-1}X'Y \right] \\ &= p\lim \left[ (X'X)^{-1}X'(Xb + e) \right] \\ &= p\lim \left[ (X'X)^{-1}X'Xb \right] + p\lim \left[ (X'X)^{-1}X'e \right] \\ &= p\lim \left[ (X'X)^{-1}X'X \right] b + p\lim \left[ (X'X)^{-1}X'(b_3 X_3 + u) \right] \\ &= b + b_3 p\lim \left[ (X'X)^{-1}X' X_3 \right] + p\lim \left[ (X'X)^{-1}X'u \right] \\ &= b + b_3 p\lim \left[ (X'X)^{-1}X' X_3 \right] \\ &= b + b_3 \mathbb{E}(X'X)]^{-1} \mathbb{E}(X' X_3) \end{align*}

Above, a key step is of course that $p\lim \left[ (X'X)^{-1}X'u \right] =0$, which happens because

$$ p\lim \left[ (X'X)^{-1}X'u \right] = (p\lim X'X)^{-1} p\lim (X'u) = [\mathbb{E}(X'X)]^{-1} \mathbb{E}(X'u) $$, since $\mathbb{E}(X'u)=0$, which holds because the original assumption is that each of the regressors are uncorrelated with $u$ (but not necessarily $e$).

Now we see that $p\lim \hat{\beta} \ne b$ whenever $\mathbb{E}(X'X_3) \ne 0$, that is whenever there is correlation between $X_1$ and $X_3$ or between $X_2$ and $X_3$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.